Epitaxial growth of 3C-SiC (111) on Si via laser CVD carbonization. Issue 3 (3rd July 2019) - Tu, Rong; Hu, Zhiying; Xu, Qingfang; Li, Lin; Yang, Meijun; Li, Qizhong; Shi, Ji; Li, Haiwen; Zhang, Song; Zhang, Lianmeng; Goto, Takashi; Ohmori, Hitoshi; et al.
ABSTRACT: A qualitative and quantitative study was performed on the carbonization temperature ( T C ) and carbonization time ( t C ) with respect to the microstructure and growth rate ( R g ) of a 3C-SiC epitaxial layer on Si (111) substrates by carbonization via laser chemical vapor deposition (LCVD). The results showed that the density and size of the voids depended strongly on T C . The voids were sealed, and thin films were formed continuously and uniformly after a carbonization time of 6 min at T C  = 1200 °C. R g was also dependent on T C, and increased from 0.43 to 1.35μm·h −1 with increases in T C from 1000 to 1200 °C. These deposition rates are 10 to 100 times greater than those of observed for conventional CVD methods.